A multi-stage flower-like MgO-based CO2 adsorbent with adjustable surface hydroxyl groups and a preparation method thereof
Patent Information
- Application Number
- CN202611177199.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
AI Technical Summary
本发明以六水合硝酸镁为镁源,以甲醇和多元醇为混合溶剂,通过溶剂热反应、惰性气氛煅烧和空气气氛煅烧制备多级类花状MgO载体,再通过浸渍-溶剂蒸发法负载LiNO3、NaNO3和KNO3混合碱金属硝酸盐,中温条件下混合碱金属硝酸盐可形成促进CO2传质和界面反应的熔融盐相,从而提高MgO基吸附剂的碳酸化反应动力学,最后经空气气氛热处理得到目标吸附剂,通过多级类花状结构、表面羟基调控和混合碱金属硝酸盐改性的协同作用,改善了MgO基材料在中温CO2吸附/脱附循环中的反应动力学和循环稳定性;
Smart Images

Figure CN122875188A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups and its preparation method, belonging to the field of functional adsorption materials technology. Background Technology
[0002] With the increasing use of fossil fuels and CO2 emissions from industrial production, the development of efficient, stable, and low-cost CO2 capture materials is of great significance for achieving carbon emission reduction. Solid adsorption, due to its advantages such as strong equipment adaptability, relatively low energy consumption, and recyclable adsorbents, has become one of the important technical routes in the field of CO2 capture.
[0003] MgO materials possess advantages such as high theoretical CO2 adsorption capacity, good thermal stability, wide availability, and low cost, making them a promising class of mesophilic CO2 adsorbents. The CO2 adsorption process of MgO typically involves carbonation, where MgO reacts with CO2 to form MgCO3. However, pure MgO still suffers from problems in practical applications, including slow reaction kinetics, low utilization of effective reaction sites, structural changes during cycling, and insufficient adsorption capacity retention, limiting its further application in mesophilic CO2 capture.
[0004] To improve the CO2 adsorption performance of MgO, existing technologies typically employ methods such as alkali metal salt modification, composite support construction, morphology control, and pore structure regulation. However, existing MgO-based adsorbents still have the following shortcomings: First, alkali metal salts are prone to migration, aggregation, or uneven distribution during cycling, leading to a decrease in the utilization rate of active sites; second, MgO supports are prone to structural collapse or pore blockage during repeated carbonation / regeneration, affecting long-term stability; and third, existing technologies lack sufficient control over surface oxygen species such as hydroxyl groups and lattice oxygen on the MgO surface, making it difficult to balance initial adsorption activity and cycling stability. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups and its preparation method. The multi-level flower-like MgO support is constructed by a methanol-polyol assisted solvothermal method, and the surface hydroxyl content, pore structure and alkali metal salt dispersion state of the MgO support are synergistically regulated by inert atmosphere calcination, air atmosphere calcination and subsequent alkali metal nitrate loading and heat treatment processes, thereby improving the adsorption performance and cycle stability of the MgO-based adsorbent in the intermediate temperature CO2 adsorption / desorption cycle.
[0006] To achieve the above objectives, the present invention is implemented using the following technical solution: On one hand, the present invention provides a multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups, comprising a multi-level flower-like MgO support and a mixed alkali metal nitrate loaded on the surface and / or pores of the multi-level flower-like MgO support.
[0007] Furthermore, the mixed alkali metal nitrate includes at least two of LiNO3, NaNO3, and KNO3; And / or, the multi-level flower-like MgO support is formed by the self-assembly of one or more of nanosheets, nanopetals, and sheets with multi-level pore structures, wherein the multi-level flower-like structure is flower-like, sheet-like flower-like, or sheet-like.
[0008] Furthermore, the loading amount of the mixed alkali metal nitrate is 5 to 40 wt% of the mass of the multi-level flower-like MgO support.
[0009] On the other hand, the present invention provides a method for preparing a multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups as described in any one of the first aspects, comprising: Magnesium-based precursors were prepared using polyol-assisted solvothermal methods. MgO / C intermediates were prepared by calcining magnesium-based precursors under an inert atmosphere. Multilevel flower-like MgO support was prepared by calcining MgO / C intermediates in air atmosphere; Mixed alkali metal nitrates were loaded onto a hierarchical flower-like MgO support and then heat-treated to obtain a hierarchical flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups.
[0010] Furthermore, the method of preparing magnesium-based precursors using polyol-assisted solvothermal methods includes: Magnesium nitrate hexahydrate was added to a mixed solvent of methanol and polyol and stirred until dissolved to obtain a magnesium salt solution. The magnesium salt solution was subjected to a solvothermal reaction, followed by cooling, centrifugation, washing, and drying to obtain a magnesium-based precursor.
[0011] Furthermore, the polyol is one or more selected from 1,4-butanediol, 1,5-pentanediol, and diethylene glycol; And / or, the parameters of the solvothermal reaction include transferring the magnesium salt solution into the reaction vessel and reacting at a temperature range of 160~190°C for 6~16 h, more preferably, the solvothermal reaction temperature is 175°C and the reaction time is 10 h; And / or, the centrifugation parameters include centrifugation at a speed of 4000-8000 rpm for 5-20 min, more preferably, the centrifugation speed is 5000 rpm and the centrifugation time is 10 min; And / or, the washing is performed by washing with anhydrous ethanol 2 to 3 times; And / or, the drying parameters include drying at a temperature range of 50~80℃ for 5~12 hours, more preferably, the drying temperature is 60℃ and the drying time is 8 hours.
[0012] Furthermore, the inert atmosphere is one or a combination of nitrogen and argon; And / or, the parameters for calcining the magnesium-based precursor in an inert atmosphere and the calcining of the MgO / C intermediate in an air atmosphere are as follows: calcination at a heating rate of 1~5℃ / min to 450~550℃, followed by holding at that temperature for 1~4h; more preferably, calcination at a heating rate of 3℃ / min to 500℃, followed by holding at that temperature for 2h.
[0013] Furthermore, the loading of mixed alkali metal nitrates onto a hierarchical flower-like MgO support includes: The multi-level flower-like MgO support is immersed in a mixed alkali metal nitrate and stirred continuously until the multi-level flower-like MgO support is evenly dispersed, so that the mixed alkali metal nitrate is in full contact with the surface and pores of the multi-level flower-like MgO support before drying. The soaking time ranges from 4 to 12 hours, more preferably 8 hours; the drying parameters include drying at a temperature range of 100 to 130°C for 8 to 12 hours, more preferably at a drying temperature of 120°C for 10 hours.
[0014] Furthermore, the surface hydroxyl content of the multi-level flower-like MgO-based CO2 adsorbent is controlled by heat treatment; The heat treatment is divided into two types. One type of heat treatment involves heating at a rate of 1-5°C / min to 430-470°C and holding for 3-8 hours to obtain a first type of multi-level flower-like MgO-based CO2 adsorbent. More preferably, the heat treatment involves heating at a rate of 3°C / min to 450°C and holding for 5 hours. The other type of heat treatment involves heating at a rate of 1-5°C / min to 480-520°C and holding for 1-4 hours. More preferably, the heat treatment involves heating at a rate of 3°C / min to 500°C and holding for 2 hours to obtain a second type of multi-level flower-like MgO-based CO2 adsorbent.
[0015] Furthermore, the first type of multi-level flower-like MgO-based CO2 adsorbent has better surface hydroxyl content and cycle stability than the second type of multi-level flower-like MgO-based CO2 adsorbent. The second type of multi-level flower-like MgO-based CO2 adsorbent has better lattice oxygen relative content and initial adsorption activity than the first type of multi-level flower-like MgO-based CO2 adsorbent.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: This invention uses magnesium nitrate hexahydrate as the magnesium source and methanol and polyol as mixed solvents to prepare a multi-level flower-like MgO support through solvothermal reaction, inert atmosphere calcination, and air atmosphere calcination. Then, a mixed alkali metal nitrate of LiNO3, NaNO3, and KNO3 is loaded through an impregnation-solvent evaporation method. Under intermediate temperature conditions, the mixed alkali metal nitrate can form a molten salt phase that promotes CO2 mass transfer and interfacial reaction, thereby improving the carbonation reaction kinetics of the MgO-based adsorbent. Finally, the target adsorbent is obtained by heat treatment in an air atmosphere. Through the synergistic effect of multi-level flower-like structure, surface hydroxyl regulation, and mixed alkali metal nitrate modification, the reaction kinetics and cycle stability of MgO-based materials in intermediate temperature CO2 adsorption / desorption cycles are improved. This invention employs a methanol-polyol-assisted solvothermal method to prepare a multi-level flower-like MgO support. The resulting support is assembled from sheet-like or petal-like units, exhibiting good pore connectivity and numerous exposed reaction sites, which is beneficial for CO2 molecule diffusion and MgO carbonation reaction. By combining inert atmosphere calcination, air calcination, and subsequent heat treatment, the morphology and surface hydroxyl content of the MgO support can be controlled. Adsorbents that appropriately retain surface hydroxyl groups can exhibit better structural stability and capacity retention during cyclic adsorption / desorption. The preparation process of this invention is simple, the raw materials are readily available, and the reaction conditions are mild. It is suitable for applications such as medium-temperature CO2 capture, MgO / MgCO3 carbonation cycle system, and CO2 removal from industrial process tail gas. Attached Figure Description
[0017] Figure 1 The images are scanning electron microscope (SEM) schematic diagrams of the MgO supports prepared in Examples 1-3 of the present invention. Specifically, a is a scanning electron microscope schematic diagram of the rose-shaped MgO support MgO-PentaDO prepared in Example 1, b is a scanning electron microscope schematic diagram of the bud-shaped MgO support MgO-DEG prepared in Example 2, and c is a scanning electron microscope schematic diagram of the flower-shaped MgO support MgO-BDO prepared in Example 3. Figure 2 The following are schematic diagrams of XPS O 1s spectra of the adsorbents prepared in Examples 1-3 of the present invention, wherein a is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-PentaDO-450 prepared in Example 1, b is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-DEG-450 prepared in Example 2, and c is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-BDO-450 prepared in Example 3; Figure 3The following are schematic diagrams of XPS O 1s spectra of the adsorbents prepared in Examples 4-6 of the present invention, wherein a is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-PentaDO-500 prepared in Example 4, b is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-DEG-500 prepared in Example 5, and c is a schematic diagram of XPS O 1s spectra of the adsorbent AMS / MgO-BDO-500 prepared in Example 6; Figure 4 The images show the infrared spectra of the adsorbents prepared in Examples 1-6 of the present invention, where a is the infrared spectrum of the adsorbents AMS / MgO-PentaDO-450, AMS / MgO-DEG-450 and AMS / MgO-BDO-450 prepared in Examples 1-3, and b is the infrared spectrum of the adsorbents AMS / MgO-PentaDO-500, AMS / MgO-DEG-500 and AMS / MgO-BDO-500 prepared in Examples 4-6. Figure 5 The diagrams above are schematic diagrams of the cyclic adsorption performance tests of the adsorbents prepared in Examples 1-3 of the present invention. In the diagrams, a is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-PentaDO-450 prepared in Example 1, b is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-DEG-450 prepared in Example 2, and c is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-BDO-450 prepared in Example 3. Figure 6 The diagrams shown are schematic diagrams of the cyclic adsorption performance tests of the adsorbents prepared in Examples 4-6 of the present invention. Specifically, a is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-PentaDO-500 prepared in Example 4, b is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-DEG-500 prepared in Example 5, and c is a schematic diagram of the cyclic adsorption performance test of the adsorbent AMS / MgO-BDO-500 prepared in Example 6. Detailed Implementation
[0018] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention. Example 1
[0019] This invention provides a method for preparing a rose-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent using 1,5-pentanediol as a polyol regulator, specifically including the following steps: (1) Preparation of rose-shaped MgO support Weigh 1 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O and add it to a mixed solvent consisting of 35 mL methanol and 11.7 mL 1,5-pentanediol. Stir magnetically at room temperature until the magnesium nitrate hexahydrate is completely dissolved to obtain a clear and homogeneous solution.
[0020] The resulting solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene (PTFE), sealed, and placed in an oven at 175°C for 10 h. After the reaction was complete, the reactor was allowed to cool naturally to room temperature. The reaction solution was then removed, transferred to centrifuge tubes, and centrifuged at 5000 rpm for 10 min. The white precipitate at the bottom was collected.
[0021] The precipitate was washed 2-3 times with anhydrous ethanol to remove residual organic solvents and soluble impurities; then the washed precipitate was dried in an oven at 60°C for 8 h to obtain the magnesium-based precursor.
[0022] The magnesium-based precursor was placed in a tube furnace and heated to 500°C at a rate of 3°C / min under nitrogen atmosphere protection, and held at that temperature for 2 h to obtain the MgO / C intermediate.
[0023] The obtained MgO / C intermediate was placed in a muffle furnace and heated to 500℃ at a heating rate of 3℃ / min under air atmosphere, and held for 2 h to obtain a rose-shaped MgO support, denoted as MgO-PentaDO.
[0024] (2) Mixed alkali metal nitrate loading Weigh 0.2 g of MgO-PentaDO support, and weigh the corresponding mass of LiNO3, NaNO3 and KNO3 according to the molar ratio of LiNO3, NaNO3 and KNO3 of 0.30:0.18:0.52, so that the total loading of the mixed alkali metal nitrate is 20 wt% of the mass of MgO-PentaDO.
[0025] LiNO3, NaNO3, and KNO3 were added to 40 mL of deionized water and stirred until completely dissolved to obtain a mixed alkali metal nitrate solution. MgO-PentaDO was then added to this solution, and the mixture was stirred continuously at room temperature for 8 h to ensure uniform dispersion of the MgO support and to fully load the mixed alkali metal nitrates onto the surface and pores of the MgO support.
[0026] The resulting suspension was transferred to an evaporating dish and dried in a 120°C oven for 10 h to allow the solvent to evaporate completely. After cooling to room temperature, the white solid powder was collected to obtain the alkali metal nitrate-supported MgO-PentaDO material.
[0027] (3) Heat treatment The above-mentioned alkali metal nitrate-supported MgO-PentaDO material was divided into two parts.
[0028] The first sample was placed in a muffle furnace and heated to 450°C at a rate of 3°C / min in air atmosphere, and held at that temperature for 5 h to obtain the first type of rose-shaped alkali metal nitrate modified MgO adsorbent, denoted as AMS / MgO-PentaDO-450. Example 2
[0029] This invention provides a method for preparing a bud-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent using diethylene glycol as a polyol regulator. The difference between this method and Example 1 is that 1,5-pentanediol is replaced with diethylene glycol to prepare a bud-shaped MgO support, denoted as MgO-DEG, and a bud-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent, denoted as AMS / MgO-DEG-450. Example 3
[0030] This invention provides a method for preparing a flower-shaped alkali metal nitrate modified MgO-based CO2 adsorbent using 1,4-butanediol as a polyol regulator. The difference between this method and Example 1 is that 1,5-pentanediol is replaced with 1,4-butanediol. The resulting flower-shaped MgO support is denoted as MgO-BDO, and the flower-shaped alkali metal nitrate modified MgO-based CO2 adsorbent is denoted as AMS / MgO-BDO-450. Example 4
[0031] This embodiment provides a method for preparing a rose-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent using 1,5-pentanediol as a polyol regulator, specifically including the following steps: Another sample from Example 1 was placed in a muffle furnace and heated to 500°C at a rate of 3°C / min in air atmosphere, and held at that temperature for 5 h to obtain a second type of rose-shaped alkali metal nitrate modified MgO adsorbent, denoted as AMS / MgO-PentaDO-500. Example 5
[0032] This invention provides a method for preparing a bud-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent using diethylene glycol as a polyol regulator, specifically including the following steps: Another sample from Example 2 was placed in a muffle furnace and heated to 500°C at a rate of 3°C / min in air atmosphere, and held at that temperature for 5 h to obtain a second type of rose-shaped alkali metal nitrate modified MgO adsorbent, denoted as AMS / MgO-DEG-500. Example 6
[0033] This invention provides a method for preparing a bud-shaped alkali metal nitrate-modified MgO-based CO2 adsorbent using 1,4-butanediol as a polyol regulator, specifically including the following steps: Another sample from Example 3 was placed in a muffle furnace and heated to 500°C at a rate of 3°C / min in air atmosphere, and held at that temperature for 5 h to obtain a second type of rose-shaped alkali metal nitrate modified MgO adsorbent, denoted as AMS / MgO-BDO-500.
[0034] The materials obtained in Examples 1-6 are characterized and their performance tested and analyzed below.
[0035] (1) Morphological characteristics The microstructure of the MgO support was observed using scanning electron microscopy, such as... Figure 1 As shown, the MgO supports obtained in Examples 1-3 all exhibit a flower-like or flower-like multi-level structure, assembled from lamellar or petal-like units, possessing numerous pores and an open structure. This structure is beneficial for improving the diffusion efficiency of CO2 molecules and increasing the contact opportunities between MgO and CO2.
[0036] (2) Characterization of surface chemical state The O1s spectra of the alkali metal nitrate-modified adsorbents prepared in Examples 1-6 were analyzed using X-ray photoelectron spectroscopy. The results are as follows: Figure 2 and Figure 3 As shown: In the AMS / MgO-PentaDO-450 sample, the hydroxyl oxygen peak area accounted for 12.54% of the total O 1s peak area; in the AMS / MgO-PentaDO-500 sample, the hydroxyl oxygen peak area accounted for 35.02% of the total O 1s peak area.
[0037] In the AMS / MgO-DEG-450 sample, the hydroxyl oxygen peak area accounted for 5.83% of the total O 1s peak area; in the AMS / MgO-DEG-500 sample, the hydroxyl oxygen peak area accounted for 33.89% of the total O 1s peak area.
[0038] In the AMS / MgO-BDO-450 sample, the hydroxyl oxygen peak area accounted for 5.41% of the total O 1s peak area; in the AMS / MgO-BDO-500 sample, the hydroxyl oxygen peak area accounted for 17.62% of the total O 1s peak area.
[0039] It can be seen that the adsorbent surface obtained by heat treatment at 450℃ has a more obvious hydroxyl oxygen correlation signal; after heat treatment at 500℃, the hydroxyl oxygen correlation signal weakens and the lattice oxygen correlation signal strengthens.
[0040] (3) Fourier transform infrared spectroscopy characterization Fourier transform infrared spectroscopy was used to analyze the surface functional groups of the alkali metal nitrate-modified adsorbents prepared in Examples 1-6. Figure 4 As shown, the results further indicate that hydroxyl-related vibrational signals exist in both the 450℃ and 500℃ heat-treated samples. The hydroxyl-related peak intensity of the 450℃ heat-treated sample is higher, which is consistent with the XPS analysis results, indicating that different treatment temperatures affect the intensity of the hydroxyl-related signal.
[0041] (4) CO2 adsorption / desorption cycle performance test Thermogravimetric analysis was used to conduct CO2 adsorption / desorption cycle tests on the adsorbent. The test conditions were as follows: adsorption temperature was 320℃, adsorption atmosphere was 50 vol% CO2 / N2 mixture, adsorption time was 2 h; desorption temperature was 450℃, desorption atmosphere was N2, desorption time was 0.5 h; and the number of cycles was 18.
[0042] Test results are as follows Figure 5 and Figure 6 As shown, the initial CO2 adsorption capacity of AMS / MgO-PentaDO-450 was 164 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 321 mg CO2 / g adsorbent, with a capacity retention rate of 195.73%.
[0043] The initial CO2 adsorption capacity of AMS / MgO-PentaDO-500 was 403 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 308 mg CO2 / g adsorbent, with a capacity retention rate of 76.43%.
[0044] The initial CO2 adsorption capacity of AMS / MgO-DEG-450 was 382 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 308 mg CO2 / g adsorbent, with a capacity retention rate of 80.63%.
[0045] The initial CO2 adsorption capacity of AMS / MgO-DEG-500 was 461 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 226 mg CO2 / g adsorbent, with a capacity retention rate of 49.02%.
[0046] The initial CO2 adsorption capacity of AMS / MgO-BDO-450 was 510 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 345 mg CO2 / g adsorbent, with a capacity retention rate of 67.65%.
[0047] The initial CO2 adsorption capacity of AMS / MgO-BDO-500 was 524 mg CO2 / g adsorbent, and the CO2 adsorption capacity after the 18th cycle was 365 mg CO2 / g adsorbent, with a capacity retention rate of 69.66%.
[0048] The results showed that AMS / MgO-450 maintained a high adsorption capacity after 18 CO2 adsorption / desorption cycles with minimal capacity decay, demonstrating good cycling stability. AMS / MgO-500 exhibited high initial adsorption activity, but its adsorption capacity decreased relatively significantly after multiple cycles.
[0049] In summary, this invention improves the reaction kinetics and cycle stability of MgO-based materials in intermediate-temperature CO2 adsorption / desorption cycles through the synergistic effects of multi-level flower-like structures, surface hydroxyl group regulation, and modification with mixed alkali metal nitrates. Specifically, the sample heat-treated at 450℃ exhibits higher surface hydroxyl content and better capacity retention, making it suitable for intermediate-temperature CO2 capture processes with high requirements for cycle stability; the sample heat-treated at 500℃ demonstrates higher initial adsorption activity, making it suitable for applications requiring high initial adsorption rates.
[0050] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A multi-level, flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups, characterized in that, It includes a multi-level flower-like MgO support and mixed alkali metal nitrates loaded on the surface and / or pores of the multi-level flower-like MgO support.
2. The multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 1, characterized in that, The mixed alkali metal nitrate includes at least two of LiNO3, NaNO3 and KNO3; And / or, the multi-level flower-like MgO support is formed by the self-assembly of one or more of nanosheets, nanopetals, and sheets with multi-level pore structures, wherein the multi-level flower-like structure is flower-like, sheet-like flower-like, or sheet-like.
3. The multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 1, characterized in that, The loading of the mixed alkali metal nitrate is 5 to 40 wt% of the mass of the multi-level flower-like MgO carrier.
4. A method for preparing a multi-level, flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups as described in any one of claims 1 to 3, characterized in that, include: Magnesium-based precursors were prepared using polyol-assisted solvothermal methods. MgO / C intermediates were prepared by calcining magnesium-based precursors under an inert atmosphere. Multilevel flower-like MgO support was prepared by calcining MgO / C intermediates in air atmosphere; Mixed alkali metal nitrates were loaded onto a hierarchical flower-like MgO support and then heat-treated to obtain a hierarchical flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups.
5. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 4, characterized in that, The method of preparing magnesium-based precursors using polyol-assisted solvothermal methods includes: Magnesium nitrate hexahydrate was added to a mixed solvent of methanol and polyol and stirred until dissolved to obtain a magnesium salt solution. The magnesium salt solution was subjected to a solvothermal reaction, followed by cooling, centrifugation, washing, and drying to obtain a magnesium-based precursor.
6. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 5, characterized in that, The polyol is one or more of 1,4-butanediol, 1,5-pentanediol, and diethylene glycol; And / or, the parameters and conditions of the solvothermal reaction include transferring the magnesium salt solution into the reaction vessel and reacting at a temperature range of 160~190°C for 6~16 hours; And / or, the centrifugation parameters include centrifugation at a speed of 4000~8000 rpm for 5~20 min; And / or, the washing is performed by washing with anhydrous ethanol 2 to 3 times; And / or, the drying parameters include drying at a temperature range of 50~80℃ for 5~12 hours.
7. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 4, characterized in that, The inert atmosphere is one or a combination of nitrogen and argon. And / or, the parameters for calcining the magnesium-based precursor in an inert atmosphere and the calcining of the MgO / C intermediate in an air atmosphere are both to raise the temperature to 450-550°C at a heating rate of 1-5°C / min and hold for 1-4 hours.
8. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 4, characterized in that, The process of loading mixed alkali metal nitrates onto a multi-level flower-like MgO support includes: The multi-level flower-like MgO support is immersed in a mixed alkali metal nitrate and stirred continuously until the multi-level flower-like MgO support is evenly dispersed, so that the mixed alkali metal nitrate is in full contact with the surface and pores of the multi-level flower-like MgO support before drying. The soaking time ranges from 4 to 12 hours; the drying parameters include drying at a temperature range of 100 to 130°C for 8 to 12 hours.
9. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 4, characterized in that, The surface hydroxyl content of the multi-level flower-like MgO-based CO2 adsorbent was controlled by heat treatment. The heat treatment is divided into two types. One type of heat treatment involves heating at a rate of 1-5℃ / min to 430-470℃ and holding for 3-8 hours to obtain a first type of multi-level flower-like MgO-based CO2 adsorbent. The other type of heat treatment involves heating at a rate of 1-5℃ / min to 480-520℃ and holding for 1-4 hours to obtain a second type of multi-level flower-like MgO-based CO2 adsorbent.
10. The method for preparing the multi-level flower-like MgO-based CO2 adsorbent with tunable surface hydroxyl groups according to claim 9, characterized in that, The first type of multi-level flower-like MgO-based CO2 adsorbent has better surface hydroxyl content and cycle stability than the second type of multi-level flower-like MgO-based CO2 adsorbent. The second type of multi-level flower-like MgO-based CO2 adsorbent has better lattice oxygen relative content and initial adsorption activity than the first type of multi-level flower-like MgO-based CO2 adsorbent.